Chapter Introduction Crossing the Iron Curtain - Bechmann Pedersen, Sune; Noack, Christian (Taylor & Francis, 2021)
Focusing on Western tourism behind the Iron Curtain, this chapter introduces the main research questions addressed in the volume: firstly, how and why Eastern Europe became a tourist destination for citizens of the West; secondly what impact this had on the development of a tourism industry in the Eastern bloc; and thirdly to what extent the experiences of Western tourists in Eastern Europe influenced mutual perceptions and Cold War stereotypes of “the other”. The chapter situates these questions in three debates in recent historiography: the history of transnational tourism, of the cultural Cold War, and of mobilities in the supposedly backward and static societies in Eastern Europe.